Deliberate Poisoning with Endosulfant Two Cases - Aktaş, Ekin Özgür; Koçak, Aytaç; Şenol, Ender; Ertürk, Süheyla; Karali, Hüseyin; Yunus, Tülge (The Bulletin of Legal Medicine, 2005)
Endosulfan is an insecticide containing chlorine and is used especially in agricultural areas. It is one of the most toxic insecticides. When one is acutely subjected to endosülfan at a toxic level, the primary effects are gastrointestinal irritation, instability of central nervous system, respiratory depression and cardiovascular system collapse. The primary effects of endosulfan were shown to be on central nervous system according to the studies and especially in all acute poisoning cases convulsion was encountered In this study, detection of endosülfan in milk boxes eliminates the possibility of its origin to be either accidental or suicide. It should be kept in mind that, the origin of fatal poisoning could be homicidal suchas in this case as but not only accidental or suicidal. These cases were presented because the manner of death were of the kind rarely encountered in the literature. Key words: Insecticide, endosülfan, deliberate poisoning.